2014
DOI: 10.1136/bjophthalmol-2014-305005
|View full text |Cite
|
Sign up to set email alerts
|

Risk characteristics of the combined geographic atrophy and choroidal neovascularisation phenotype in age-related macular degeneration

Abstract: Aim To investigate the risk characteristics of the combined geographic atrophy (GA) and choroidal neovascularization (CNV) phenotype of age-related macular degeneration (AMD) compared to GA or CNV. Methods Patients with advanced AMD were identified and divided into three groups using multimodal imaging: patients with GA in at least one eye, patients with CNV in at least one eye, and patients with simultaneous GA and CNV in at least one eye. Epidemiologic and clinical factors were gathered from patient questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
0
14
0
6
Order By: Relevance
“…In our patients, these findings eventually developed in approximately two-thirds of the included eyes. GA is characterized by loss of choriocapillaris, RPE, and retinal outer layers [43,44]. GA is one of the important points of consideration while treating type 3 neovascularization, as eyes with type 3 neovascularization are at a high risk of GA development [45].…”
Section: Discussionmentioning
confidence: 99%
“…In our patients, these findings eventually developed in approximately two-thirds of the included eyes. GA is characterized by loss of choriocapillaris, RPE, and retinal outer layers [43,44]. GA is one of the important points of consideration while treating type 3 neovascularization, as eyes with type 3 neovascularization are at a high risk of GA development [45].…”
Section: Discussionmentioning
confidence: 99%
“…Another study found no difference in CFH allele frequencies between subjects with the combined GA/CNV phenotype and those with GA or CNV alone, but contrary to the Grob. et al study, there was a lower frequency (albeit not statistically significant) of the ARMS2 risk allele among patients with the combined GA/CNV form [4]. It appears that the combined phenotype does not have a unique genetic profile, although further research remains to be done.…”
Section: The Combined Ga/cnv Phenotype Of Amdmentioning
confidence: 99%
“…However, neither of the MPS Group studies focused on the combined GA/CNV form, and few patients with GA were included [35, 36]. One recent study showed that the combined GA/CNV entity tends to occur at an older age than GA or CNV alone and is associated with late AMD in the fellow eye, suggesting that the combined phenotype may be a later stage along the same spectrum of disease [4]. There were no differences in rates of hypertension, diabetes, or dyslipidemia, or in smoking status or family history of AMD, between the combined phenotype group and the group with either GA or CNV [4].…”
Section: The Combined Ga/cnv Phenotype Of Amdmentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread nature of dry AMD [ 4 , 5 ] and the unpredictability of its progression to choroidal neovascularization (CNV), geographic atrophy (GA), or both with sight threatening implications, continues to draw the interest of many investigators to better understand its pathogenesis. The association of dry AMD with the late AMD stages of CNV and GA has intrigued various researchers, and a possible underlying “unified” vascular abnormality has been suggested in its pathogenesis [ 6 9 ]. Advances in multimodal imaging have enhanced our understanding of dry AMD, including the identification of high risk features for its progression to GA and CNV, by facilitating high quality in vivo imaging.…”
Section: Introductionmentioning
confidence: 99%